The culture and social institutions of ancient Iran - Dandamaev, Muhammad A. (Cambridge)
xv, 463
Keywords: "After reviewing knowledge of Iron Age Iran, the authors look in detail at the highly developed social institutions of the Achaemenid Empire, most notably at state administration, agrarian relations, monetary systems, slavery and trade. A wide-ranging discussion of that culture covers such topics as the religion of the Ancient Iranians, ethnic and cultural contacts with the Achaemenid Empire, and superstitious and scientific practices in the ancient Near East during the sixth to the fourth centuries B.C." --